2019
DOI: 10.1128/jvi.00876-19
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of Ovine Lung to Infection with Jaagsiekte Sheep Retrovirus

Abstract: Ovine pulmonary adenocarcinoma is a chronic respiratory disease of sheep caused by jaagsiekte sheep retrovirus (JSRV). OPA is a significant economic problem for sheep farmers in many countries and is a valuable animal model for some forms of human lung cancer. Here, we examined the changes in host gene expression that occur in the lung in response to JSRV infection. We identified a large number of genes with altered expression in infected lung, including factors with roles in cancer and immune system function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 80 publications
5
24
1
Order By: Relevance
“…As previously described 54 , identification of enriched KEGG pathways and biological processes in the protein list was performed with Database for Annotation, Visualization and Integrated Discovery (DAVID) software (v6.8) 29 , 55 , 56 . KEGG pathway database contains regulatory and metabolic pathways, representing global knowledge on molecular interactions and reaction networks.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described 54 , identification of enriched KEGG pathways and biological processes in the protein list was performed with Database for Annotation, Visualization and Integrated Discovery (DAVID) software (v6.8) 29 , 55 , 56 . KEGG pathway database contains regulatory and metabolic pathways, representing global knowledge on molecular interactions and reaction networks.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms involved in JSRV Env-induced transformation have not been fully elucidated, but several studies have shown the activation of signalling pathways that control cellular proliferation, including phosphatidylinositol 3-Kinase (PI3K)-Akt and mitogen-activated protein kinase (MAPK) [ 3 , 55 ], and additional pathways, including the AGR-2-YAPI-AREG axis, may also contribute to oncogenesis in this disease [ 55 ]. Other mechanisms, such as targeted integration of JSRV, cannot be totally excluded [ 3 ].…”
Section: Ovine Pulmonary Adenocarcinomamentioning
confidence: 99%
“…As previously described 46 , identi cation of enriched KEGG pathways and biological processes in the protein list was performed with Database for Annotation, Visualization and Integrated Discovery (DAVID) software (v6.8) 27,47,48 . KEGG pathway database contains regulatory and metabolic pathways, representing global knowledge on molecular interactions and reaction networks.…”
Section: Protein Function Annotation and Pathway Analysismentioning
confidence: 99%